The Gender Aspect of the English Language. Should We Teach Gender Neutrality in the Classroom? - Grigoryeva, Leona; Nazmieva, Elmira (Journal of Education Culture and Society, 2023)
Aim. This article is aimed at the study of different aspects of gender linguistics in the English language, namely, the grammatical category of gender, gender vocabulary and phraseology, male and female differences in using language, the problem of gender neutrality teaching in English. Methods. The article is based on the study and review of research works in the fields of cultural studies, linguistics, and sociology. The paper summarises the current state of understanding on the topic and makes contribution to the field. Results. In this paper the grammatical gender of English is studied, examples of lexical units, phraseology, proverbs, and sayings are given, and differences in speech between men and women are described, forms of gender-neutral English are presented. The results of research clearly show that in the past English used not to be a gender-neutral language. Nowadays, we can observe that changes in cultural views influenced by feminism in the English-speaking countries have led to changes in the language itself. Conclusions. English has become one of the first languages in the world in which gender neutrality has become predominant. We think since gender-neutrality is highly valued in the English-speaking society, it must be taught to learners of English in different countries since the primary aim of learning a foreign language is communication which always includes a cultural component.